Maximizing utilization of fleet in cargo operation with special reference to Felda Transport Corporation / Zulazli Hashim - Hashim, Zulazli (1988)
Proper management and efficient planning are essential in achieving a fully maximize utilization of fleet. The scope of study that being look into in order to obtain fully maximized utilization of fleet involved the present trend of demand services, method of routein^ and schedulling, and the fleet availability and requirements. The study will reveale the strengths and weaknesses of the company in their operation.